Indices of globalization as instruments for its measurement - Bilous, Svetlana (Видавництво Львівської політехніки, 2011)
Globalization, its consequences, and further implications are one of the most discussed topics nowadays and with attempts to define this notion it is measured qualitatively and quantitatively. And taking into account multidimensionality of globalization, its measuring process still appears to be a challenge for scientists. This article aims at the analysis of contemporary ways of measurement of globalization giving comparative analysis of the existing indices of globalization that is preceded by the general principles of index calculation.
Keywords: globalization; globalization indices; dimensions; variables; weights; restrictions